The relationship between orthodontic treatment and temporomandibular disorders: A dental specialists' perspective - Dheaa H. AL-GROOSH; Mushriq ABID; Ahmed Kassem SALEH (Dental Press Editora, 2022)
ABSTRACT Introduction: The relationship between temporomandibular disorders (TMDs) and orthodontic treatment/malocclusion has changed from a cause-and-effect association to an idea without sufficient evidence. Objective: This survey was designed to assess the beliefs of different disciplines - orthodontists, oral surgeons, and oral medicine specialists - on the relationship between TMDs and orthodontic treatment, with regard to treatment, prevention and etiology of TMDs. Method: A survey in the form of questionnaire was designed and distributed to 180 orthodontists, 193 oral surgeons and 125 oral medicine specialists actively involved in treating TMDs. The questionnaire aimed to collect basic information about each participant and their beliefs, and clinical management of patients with TMDs. Results: Halve of the responding orthodontists and most of the oral surgeons (69.9%) were male participants, whereas the majority of oral medicine specialists (83.3%) were female respondents. The participants' age ranged from 29 to 58 years. The majority of orthodontists believes that there is no relationship between orthodontic treatment and TMDs, and that orthodontic treatment does not provoke TMDs or prevent the onset of the disorder. However, oral surgeons and oral medicine specialists have different and conflicting opinions. Most surgeons tended to treat those patients, while most of the other two disciplines tended to seek an interdisciplinary approach. Chi-square test was done to find an association between the referral status and specialists' experience, and to compare between the different disciplines' belief. Conclusions: Orthodontist's beliefs were in accordance with the scientific evidence, whereas most oral surgeons and oral medicine specialist believed that orthodontic treatment may provoke TMDs. Therefore, continuing program series development is important to embrace the concept of the multidisciplinary team approach and improve the health care and quality of life for those patients.